The Effect of Remuneration on Work Ethic and Employee Performance at UIN North Sumatra: Empirical Analysis - Fahrul Rizal; Faridah (Penerbit Merdeka Kreasi, 2025)
This study aims to analyze the influence of remuneration on work ethic and employee performance at the State Islamic University of North Sumatra (UIN-SU). Remuneration as a form of financial compensation has an important role in encouraging employee morale and productivity. Nevertheless, performance improvement does not only depend on material incentives, but is also influenced by internal work values such as work ethic. This study uses a quantitative approach with Pearson's correlation technique and involves 45 structural employees as respondents. The main instrument used is a questionnaire that has gone through validity and reliability tests. The results showed that remuneration had a significant influence on work ethic with a correlation value of 0.304 (significant at the level of 5%). Meanwhile, remuneration also has a significant effect on employee performance with a correlation value of 0.553 (significant at the level of 1%). The most prominent finding was that work ethic had the most dominant influence on employee performance, with a correlation value of 0.887 (significant at the level of 1%). These results show that although remuneration is important as a motivational tool, work ethic has a greater role in determining employee overall performance. The implications of these findings emphasize the importance of developing a fair and transparent remuneration system, accompanied by a strong value building strategy and work culture. In the context of Islamic higher education institutions such as UIN-SU, a work ethic based on the value of worship and social responsibility needs to be strengthened in order to achieve optimal and sustainable performance.